Comparative Growth Rates of Cultured Zooxanthellae and the Effects of Temperature and Salinity - Patthanasiri, Kamonphon; Lirtwitayaprasit, Thaithaworn; Yeemin, Thamasak; Thongcamdee, Ing-on (Journal of Fisheries and Environment, 2022)
Dinoflagellates of the genus Symbiodinium form symbioses with a variety of hosts including hard corals, sea anemones, soft corals, and giant clams. Environmental stresses, especially elevated temperature and decreased water salinity, impair zooxanthellae (Symbiodinium sp.) and cause coral bleaching. To determine the role of temperature and salinity on zooxanthellae, this study was conducted on zooxanthellae isolated from seven marine invertebrate hosts: mushroom coral (Fungia fungites), cauliflower coral (Pocillopora damicornis), sea anemone (Epiactis sp.), soft coral (unidentified), staghorn coral (Acropora millepora), honeycomb coral (Goniastrea sp.) and giant clam (Tridacna squamosa). The growth response of axenic culture was observed at three levels of temperature (27 ºC [control], 30 ºC and 33 ºC) in combination with three levels of salinity: 10, 20, and 30 (control) psu. Cells were sampled and enumerated every two days for 14 days. The results showed that the main effects of host, salinity and temperature each significantly determined growth of zooxanthellae while the interactions between host and temperature and between salinity and temperature were significant. Specific growth rates of zooxanthellae grown in four different combinations of temperature and salinity ranged between 0.371±0.198 and 0.683±0.074 day-1. At 27 ºC and 30 ºC, with a salinity of 10 psu, and at 33 ºC with all salinity levels, most cells died before the end of the experiment. These results suggest that high temperature (33 ºC) and low salinity (10 psu) strongly affect the growth rate of zooxanthellae, and that the combination of high temperature and low salinity also have synergistic effects on the growth of zooxanthellae.